(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Itis a fact that mood-state knowledge is of particular relevance for theunderstanding of consumer behavior. The belief that it may be affected by thecontent of marketing communication and the context in which thesecommunications appear was the basis upon which this research was conducted.This study is essentially an experimental study where a between-subject designwas employed. A total of three hundred and twenty subjects were used in theexperiment. Unlike some previous advertising research (e.g. Kim and Biocca,1997) utilizing existing adverts, specifically design adverts were made for thestudy. Standardized 10 minute film clips were used to induce a negative orpositive mood. Two scales - attitude towards using advertised products andintention to try advertised products - were employed to measure advertisingeffectiveness. The result revealed that subjects in the induced positive mood group have a more positive attitude and greater intention totry advertised products when compared with subjects in the induced negative mood group. This suggests thatadvertisers should present adverts in a context that elicits happiness’.